2016
DOI: 10.4236/ojmh.2016.62006
|View full text |Cite
|
Sign up to set email alerts
|

Using the Markov Chain for the Generation of Monthly Rainfall Series in a Semi-Arid Zone

Abstract: Numerous methodologies have been developed in the literature for the generation of rain. However, in semi-arid areas where the irregularity of rain is contrasted, the question of the applicability of these models is still relevant. The objective of this article is to propose a development method of stochastic generator of monthly rainfall series. The present work is based on the modeling of the occurrence and the quantity of rain in a separate way. The occurrence is treated in two stages. The first step consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The annual potential evapotranspiration rate is estimated to be around 1460 mm. [12] Monthly rainfall -Sidi Saad Station [13] Monthly minimum, average and maximum temperature curve in Kairouan [14] Figure 3 Precipitation and temperature in the study area [13 14]…”
Section: Climate Of the Kairouan Regionmentioning
confidence: 99%
“…The annual potential evapotranspiration rate is estimated to be around 1460 mm. [12] Monthly rainfall -Sidi Saad Station [13] Monthly minimum, average and maximum temperature curve in Kairouan [14] Figure 3 Precipitation and temperature in the study area [13 14]…”
Section: Climate Of the Kairouan Regionmentioning
confidence: 99%
“…Some of studies presented the weather forecasting as shown in Table 1. Among them include: estimation of the rainfall sequences during the rainy season in Kurdufan [30], rainfall prediction at the Daspalla Region in Odisha, Eastern India [31] for crop planning, daily rainfall occurrence forecasting in Peninsular Malaysia [32], the rainfall estimation during monsoon season over major station in Gangetic West Bengal [33], and a stochastic generator of monthly rainfall series in Tunisia [34]. In the study [35], Markov chain model with weights was applied to predict Standardized Precipitation Index (SPI) drought intensity by using standardized self coefficients as weights.…”
Section: Markov Chain (Mc)mentioning
confidence: 99%